Implications of climate change for water surplus and scarcity and how that affects agricultural sustainability in Hungary - Sadler, Edward; Baker, John; Ringler, Claudia (Agricultural Research Institute of the Hungarian Academy of Sciences, 2011)
Prepared for the AGRISAFE Final Conference, March 21-23, 2011, Budapest, Hungary.